The Legislative Complexities of Municipal Real Estate Transactions in the Context of Social Value Creation - Emsley, Liezl (Department of Construction Economics and Management, 2025)
Legislation governing the sale and lease of immovable property by South African municipalities to third parties is extensive and multi-faceted. Different pieces of legislation are applicable, which specify several requirements to be complied with before a municipality enters into a sale or lease transaction. Compliance with some of these requirements are time-consuming and there are instances of overlap. While the requirements stipulate how a municipality should transact when undertaking immovable property transactions, consideration must also be given to overall municipal objectives and mandate, as provided for in the Constitution. The central theme of these objectives is the delivery of social value to the local community. This dissertation aims to determine to what extent legislative requirements applicable to the sale and lease of municipal immovable property to third parties support the realisation of social value objectives, as provided for in the Constitution. The study has three main objectives: a. First, to identify the legislation applicable to municipal immovable property transactions and to determine the objectives of the legislation relating to municipal immovable property transactions. b. Second, to examine the extent to which social value objectives are achieved through municipal immovable property transactions. c. Third, to investigate whether the legislation and processes relating to municipal immovable property transactions may be improved to better facilitate social value delivery. These objectives are considered by investigating and analysing the processes followed at two South African metropolitan municipalities when undertaking immovable property transactions. The study identifies and considers both the general challenges experienced by municipal officials regarding these transactions, as well as specific challenges faced in relation to the application of the legislation. The study illustrates how the legislative requirements, aimed at providing fairness and transparency, may inadvertently discourage social value creation. Recommendations are made to streamline and simplify the transaction process.